Electrochemical sensor highly selective for estradiol valerate determination based on a modified carbon paste with iron tetrapyridinoporphyrazine - Batista, Isabelle V.; Lanz, Marcos R. V.; Dias, Iara L. T.; Tanaka, Sonia M. C. N.; Tanaka, Auro A.; Sotomayor, Maria Del Pilar Taboada [UNESP] (Royal Soc Chemistry, 2008)
This work reports the use of iron tetrapyridinoporphyrazine (FeTPyPz) as a highly selective catalyst in the construction of an electrochemical sensor for estradiol valerate (EV) determination. The sensor was prepared by modifying a carbon paste with FeTPyPz. The best results were obtained in a mixture of acetonitrile (MeCN) and 0.1 mol L(-1) phosphate buffer solution (pH 6.0) in a volume ratio of 47 : 53. A linear response range was observed between 45 and 450 mmol L(-1) with a sensitivity of 12160 +/- 306 mu A L mol(-1) and quantification and detection limits of 45 and 13 mmol L(-1), respectively. The repeatability, expressed as the relative standard deviation (RSD) for n = 10, was 5.9% ([EV] = 50 mu mol(-1)). The reproducibility (RSD) for the sensor construction was better than 4% and the operational stability (RSD) over 50 measurements was 1.8%. A detailed investigation regarding the selectivity and electrochemical characteristics was carried out. Finally, in a first step to evaluate the application potential of the sensor, it was successfully applied to determine EV in a commercial formulation.